Reflection of Rhetorical Pattern in The Introduction of Academic Research Reports - Huda, Tanzil (Sebelas Maret University, 2016)
There exists a reciprocal relationship among thought, culture, and language. The relationship is clearly seen in the form of rhetoric. However, rhetoric is different from culture to culture. Certainly, this principle gives a big implication to English teaching as a foreign language. This recent study aimed at investigating the way Indonesian writers establish their rhetoric reflected in the introduction chapter of English academic reports (theses). The study also tried to investigate type of rhetoric of Indonesian reflected in the introduction of English theses. The data were collected by using the technique, namely documentation and text analysis and analysed by the researcher on the basis the scientific writing agreement model especially that is introduced by Swales and Connor & Lauer model. The result showed that Indonesian writers establish their rhetoric reflected in the introduction of English theses in an appropriate manner of scientific writing. Besides, the rhetoric applied by Indonesian writer in the introduction of English theses has followed deductive type of reasoning